2020
DOI: 10.19171/uefad.635508
|View full text |Cite
|
Sign up to set email alerts
|

Recycling From the Perspective of Pre-School Children

Abstract: Çocukların çevrelerine karşı olumlu tutum ve davranışlar kazanmaları ve bunların gelecekteki yaşantılarına temel oluşturması bakımından okul öncesi dönem kritik bir öneme sahiptir. Okul öncesi dönemde verilecek çevre eğitimi çocukların çevresel farkındalık ve tutumları üzerinde etkilidir. Çevre eğitiminin önemli bileşenlerinden biri geri dönüşümdür. Bu araştırma okul öncesi dönemdeki çocukların geri dönüşüm konusundaki farkındalıklarını araştıran nitel bir çalışmadır. Araştırmaya 3-6 yaş arasında ve bir okul ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a study conducted by Erdaş Kartal and Ada (2020) to determine recycling from the perspective of preschool children, it was found that children in the 5-year-old age group included symbols related to recycling bins, separation of garbage and recyclable materials in their drawings more than children in younger age group. Similar to the findings of this study, which was conducted to examine the recycling perceptions of 5-6year-old children attending preschool education institutions, it was found that children included recycling bin figures in their drawings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted by Erdaş Kartal and Ada (2020) to determine recycling from the perspective of preschool children, it was found that children in the 5-year-old age group included symbols related to recycling bins, separation of garbage and recyclable materials in their drawings more than children in younger age group. Similar to the findings of this study, which was conducted to examine the recycling perceptions of 5-6year-old children attending preschool education institutions, it was found that children included recycling bin figures in their drawings.…”
Section: Resultsmentioning
confidence: 99%
“…Including more recycling-oriented acquisitions in the preschool education program, expanding recycling projects to target preschool children, planning the trainings to be held in a practical way, and improving the knowledge and application skills of teachers who will carry out the applications on recycling will improve the awareness of children in this period about recycling (Erdaş Kartal & Ada, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation